2017
DOI: 10.1116/1.4982643
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical response of polyvinyl alcohol-gelatin theta-gels for nucleus pulposus tissue replacement

Abstract: Intervertebral disk degeneration is one of the most significant contributors to low back pain. Thus, there is significant interest in designing new treatments and nucleus pulposus (NP) tissue replacements. Herein, the authors propose a biosynthetic material, comprised of a polyvinyl alcohol (PVA) and gelatin theta-gel, as an acellular NP tissue replacement. Theta-gels form during the solidification of PVA and gelatin (phase I), and the phase separation of a disklike short-chain polyethylene glycol (PEG, phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…(5-9) Theta-gels, PVA hydrogels formed in the presence of a porogen, take on a unique structure, with the lower molecular weight porogen and higher molecular weight PVA separating into two distinct phases during the thermal transition, resulting in enhanced crystallinity in the denser PVA-abundant regions. (10)(11)(12) The porogen can later be removed through dialysis, resulting in macro-pores in a rigid PVA network. (11,12) PVA hydrogels can also be formed through cryo-processing, during which the mechanical properties can be tuned through subsequent freeze-thaw cycles, resulting in cryo-gels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5-9) Theta-gels, PVA hydrogels formed in the presence of a porogen, take on a unique structure, with the lower molecular weight porogen and higher molecular weight PVA separating into two distinct phases during the thermal transition, resulting in enhanced crystallinity in the denser PVA-abundant regions. (10)(11)(12) The porogen can later be removed through dialysis, resulting in macro-pores in a rigid PVA network. (11,12) PVA hydrogels can also be formed through cryo-processing, during which the mechanical properties can be tuned through subsequent freeze-thaw cycles, resulting in cryo-gels.…”
Section: Introductionmentioning
confidence: 99%
“…(10)(11)(12) The porogen can later be removed through dialysis, resulting in macro-pores in a rigid PVA network. (11,12) PVA hydrogels can also be formed through cryo-processing, during which the mechanical properties can be tuned through subsequent freeze-thaw cycles, resulting in cryo-gels. (13)(14)(15) During cryo-gel fabrication, the formation and expansion of ice crystals within the PVA solution (or hydrogel for repeated freeze-thaw cycles) results in PVA densification in the material, increasing the overall organization and crystallinity of the material, thus increasing PVA rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…However, degradation of GT is fast in the body temperature . To overcome this problem, we used another polymer (PVA) to stabilize GT . Therefore, by combining GT and PVA in this study, we enjoy both GT and PVA characteristics, and results showed that the GT/PVA scaffold had improved cell behavior.…”
Section: Discussionmentioning
confidence: 99%
“…reported the preparation of PVA theta gel where polyethylene glycol (PEG) serves as porogen and is removed through dialysis after phase separation. [ 64 ]…”
Section: Physicochemical Properties Of Pva and Hydrogel Preparationmentioning
confidence: 99%